Novel piperine-carboximidamide hybrids: design, synthesis, and antiproliferative activity via a multi-targeted inhibitory pathway - Lamya H. Al-Wahaibi; Mohamed A. Mahmoud; Yaser A. Mostafa; Ali E. Raslan; Bahaa G. M. Youssif (Taylor & Francis Group, 2023)
A new series of piperine-carboximidamide hybrids VIa-k was developed as a new cytotoxic agent targeting EGFR, BRAF, and CDK2. The antiproliferative effect against four cancer cells was investigated against erlotinib. Hybrids VIc, VIf, VIg, VIi, and VIk have the highest antiproliferative activity. Compounds VIc, VIf, VIg, VIi, and VIk inhibited EGFR with IC50 values ranging from 96 to 127 nM. Compounds VIf and VIk had the most potent inhibitory activity as BRAFV600E (IC50 = 49 and 40 nM, respectively) and were discovered to be potent inhibitors of cancer cell proliferation (GI50 = 44 and 35 nM against four cancer cell lines, respectively). Compound VIk, the most effective derivative as an antiproliferative agent, demonstrated potent anti-CDK2 action with an IC50 value of 12 nM, which is 1.5-fold more potent than the reference dinaciclib. Finally, VIc, VIf, and VIk have a high capacity to inhibit LOX-IMVI cell line survival.